Efforts to Improve Student Learning Outcomes in Islamic Religious Education Learning with a Contextual Approach - Aisyah; Maisarah (MADINA : Journal of Islamic Studies, 2024)
Based on the initial data obtained by students of class IX.1 SMP Negeri 1 Bandar Baru, it can be seen that their learning outcomes are still far from expectations, student learning completeness is still below 50% and student learning motivation is still very low. This is likely due to the lack of variety in the approaches and learning methods used by teachers in implementing the learning process. This study aims to determine and test the extent to which the application of the contextual learning approach can improve the learning outcomes of students of class IX.1 SMP Negeri 1 Bandar Baru. This type of research is classroom action research. The objects of this study were students of class IX.1 SMP Negeri 1 Bandar Baru totaling 26 people. Data were collected using test and non-test techniques, observation sheets, questionnaires and field notes, then the data obtained were described and analyzed using comparative descriptive analysis techniques for quantitative data. Comparative descriptions were carried out by comparing the results of daily tests starting from the initial conditions of cycle 1 and cycle 2 values, while qualitative descriptive analysis was guided by the results of observations and reflections for each cycle. The findings of this study indicate that using a contextual learning approach in class IX.1 of SMP Negeri 1 Bandar Baru has been proven to be able to improve student learning outcomes. This can be proven from 26 students, in cycle I 18 people or 71.5% completed and in cycle II increased to 21 people or 82.3%. Thus it can be concluded that using a contextual learning approach can significantly improve student learning outcomes.